A MODERNIZATION PROPOSAL FOR ENGLISH LANGUAGE TEACHER TRAINING PROGRAMS IN TURKIYE - Dr. Ahmet, Önal (Видавництво НДУ ім. М. Гоголя, 2025)
This article is based on the findings of two research articles conducted by the author and his colleague (Önal, 2023; Önal & Özdemir, 2024) and investigates English language teaching (ELT) as well as teacher training practices in Türkiye, emphasizing the efficiency of undergraduate ELT programs in terms of preparing teachers for teaching at different school levels. Türkiye’s monolingual status and limited exposure to English present certain challenges, with most high school graduates achieving only A1+ or A2 proficiency on the CEFR scale. ELT teacher training processes follow a structured pathway, beginning with a centralized university entrance exam focused on reading skills, leading to a four-year undergraduate program, and concluding with a public personnel selection exam for state school employment. Despite these structured pathways, findings suggest significant gaps in preparing teachers for various educational levels, particularly pre primary and university levels. Quantitative and qualitative data collected from 76 in-service teachers and 192 pre service teachers revealed mixed perceptions. While training for teaching at primary and secondary levels is deemed satisfactory, preparation for teaching at pre-primary, high school, and university levels remains inadequate. A slight majority of pre-service teachers opposed restructuring undergraduate programs into specialized tracks for young learners versus teenagers/adults, citing overall satisfaction with the current form of training. However, in-service teachers largely supported this reform, arguing that specialization aligns better with the unique needs of different learner age groups and enhances pedagogical effectiveness. The two studies highlight the incongruence between theoretical and practical training in teacher training programs. The present study underscores the need for reforms to address the varying requirements of teaching different age groups. Additionally, a significant majority of in-service teachers advocated for targeted in-service training (INSET) when transitioning to new school levels, emphasizing its role in reducing adaptation challenges and fostering professional growth. To sum up, the findings call for periodic revisions to the structure and content of ELT teacher training programs in Türkiye, adopting age-appropriate methodologies and aligning with Ministry of National Education standards to ensure more effective preparation for diverse educational contexts.
Keywords: modernization in teacher training; educational reform; teacher training programs; teaching English to diverse age groups